Motivation, purpose, and purchasing frequency of honey consumption in West Java. Issue 1 (December 2021) - Purnomo, D; Bunyamin, A; Gunawan, W; Faizah, N A; Danuwidjaja, T G; Rohman, L N; Annisa, R
Abstract: Indonesia is home to the greatest diversity of social bees in all over Asia, particularly species of the genus Apis . Thus, expanding the apiculture industry for commercial development is highly considerable. Although this industry has not become a special concern, the products of this industry are very popular among the Indonesian people, both for health, lifestyle, and other benefits. Research plays an essential role for good decision making, however, there is little research related to honey marketing in Indonesia. In this study, we observed the honey consumption of 246 respondents living in West Java by using online questionnaires and Decision Tree Classification to contribute to honey marketing research. This research shows that the motivation of the respondents in buying honey was merely for health reasons and the main purpose was for personal consumption. As for purchasing frequency, 86% of respondents purchased honey more than once a month. Then, a classification model of honey purchasing frequency based on respondents' demographics which has an accuracy of 70.3% was built. The study results should be considered by the food industry and honey producers to emphasize consumer behaviour to formulate a better marketing strategy.